Community-Based Disaster Preparedness for Risk Reduction in Pancanegara Village, Banten Province - Amaliyah, Fina Fitratun; Putri, Dian Aditya Mandana; Syarhuddin, Irham (Universitas Pahlawan Tuanku Tambusai, 2026)
Pancanegara Village in Banten Province is prone to floods and landslides as a result of sand mining activities, river flow dynamics, and the presence of water reservoirs. This community service initiative aims to improve disaster preparedness by utilizing a community-based disaster risk reduction strategy. The program was carried out through participatory approaches, such as disaster awareness training, participatory risk assessment, the formation of a Community Disaster Working Group (POKJA), catastrophe simulation exercises, and action plan formulation. The Sultan Maulana Hasanuddin State Islamic University of Banten's KUKERTA program collaborated with the Republic of Indonesia's National Zakat Agency to carry out the activities. The findings suggest increased community awareness, institutional coordination, and practical disaster response capacity, notably in terms of evacuation planning and early warning methods. Disaster preparedness is integrated into ordinary community routines, demonstrating the potential for long-term risk reduction. This program emphasizes the value of university-community relationships in implementing local resilience in disaster-prone rural areas.